STRATEGI PENGEMBANGAN PENGOLAHAN HASIL PERIKANAN DI KABUPATEN DONGGALA - Dafina Howara (Universitas Tadulako, 2013)
This paper examines the strategy that offered to develop domestic enterprises in the fish processing of Donggala regency. Data analysis used SWOT analysis. The results of the research showed that strategy for the development are: (1) Community empowerment through human resource development, product diversification and the creation of a healthy and a good market, (2) development of government agencies (Fisheries), Fostering the potential for protection and surveillance of coastal areas, (3) Building partnerships and networking in order to develop the business and development of household-scale fish processing business, and (4) development of marketing infrastructure and processing of fishery products. Key Words : Donggala, fish processing, strategy development.